A justiça militar e a democracia no Brasil: o empoderamento da magistratura civil da justiça militar e tadual - Marcelo Adriano Menacho dos Anjos (2014)
The theme of this work is Military Justice and democracy in Brazil. Initially, an incursion through political theory and the fundamental values of democracy, liberty and equality is done: Rawlss theory of Justice and the existence of a Military State Justice as an inequality that should establish itself either as the manifestation of selfishness and true injustice, while providing for the need of few, or as working for the benefit of all citizens; the monopoly of the legitimate use of violence by the State, which is a task of the police; a militarized police force and their function to perform policing and law enforcement among civilians, thus entailing the need to effectively control their performance as a safeguard to protect human rights and as a contribution for the promotion of social justice. The research seeks to find the parameters to be established for the Military State Justice for it to become the main accountability agency for the military police force and its activities and, therefore, be inserted in the context of democratic justice working towards performing the duty of democratic civilian control over the military, while enjoying the required legitimacy before civil society and occupying the most adequate space in the criminal justice system. The Judiciary Power as a political power and the history of the Military Police as a prerogative of the Brazilian military men are herein analyzed. Finally, as the Minas Gerais State Military Police plays a relevant role in the normative elements of the research, a case study is made on the institution, its history and institutional trajectory from its creation to today. From the case study originates the hypothesis of empowerment of the civilian magistracy in the State Military Justice, a hypothesis which is confirmed by the analysis of normative evidences that consist in the following legal diplomas: the Special Civil and Criminal Courts; the act that transferred the judging processes of first-degree murder against civilians from the Military Justice to Jury Trials; the torture act; the Minas Gerais State Military Ethics and Discipline Code and, finally, Constitutional Amendment no. 45/2004 and legal diplomas that triggered the empowerment of civil magistracy in the State Military Justice, thus contributing to its legitimacy and positioning as a democratic citizen justice. In addition to the above mentioned evidences, the research also produces others that provide for the expansion of the criminal competence at first instance, and for greater representation of the civil magistracy at the second instance of the State Military Justice.